Construction of coastline shelterbelts and assessment of their environmental effects in Yuyao, China. (10th July 2018) - Shan, Qihua; Zhang, Jianfeng; Sun, Shiyong; Chen, Guangcai; Zhang, Handan; Shen, Liming
Abstract: There is 18, 000 km of coastline in China. It is extremely important to construct coastal shelterbelts as they have a unique and irreplaceable role in the prevention and mitigation of natural disasters and in maintaining the ecological balance of coastal regions. A coastal shelterbelt was constructed near Yuyao City, Zhejiang Province, and three plots (wasteland, farmland, and forest) were studied to investigate the effects of environmental factors on the diversity of herbaceous plants. The environmental benefits were analyzed by field surveys and soil sampling. A total of 31 species from 30 genera and 14 families of halophyte and salt‐tolerant grasses were found in the survey area. The wasteland included 21 species from 20 genera and 9 families, whereas the shelterbelt forest had 19 species from 19 genera and 8 families, with Poaceae and Asteraceae dominating. Moreover, the Sørensen coefficient for the shelterbelt forest and wasteland was 65 and that for the shelterbelt forest and farmland was 55.56. Additionally, the salinity decreased from 0.52% to 0.02% after 2 years, similar to the value for farmland that has been cultivated for decades. The organic matter content increased from 5.1 to 9.5 g/kg, and the total nitrogen content increased from 0.34 to 0.47 g/kg. We concluded that coastline shelterbelts could be successfully established on the muddy coast. With coastline shelterbelts growing, the structure and diversity of herbaceous plants were affected, and the soil conditions were improved. Therefore, the construction of shelterbelt forest would improve the coastal landscape and enhance soil properties, accelerating the succession of herbaceous plants.